For Love of the World : Essays on Nature Writers - Paul, Sherman (Book collections on Project MUSE., 1992)
Along with poets, philosophers, and deep ecologists, nature writers-who may be something of all three-address the world alienation of Western civilization. By example as well as with words, they teach us to turn from the self to the world, from ego to ecos. In these deeply felt meditative essays, Sherman Paul contemplates the cosmological homecoming of nature writers who show us how to reenter the world, participate in it, and recover respect for it. In For Love of the World Sherman Paul considers Thoreau, John Muir, and Aldo Leopold, major writers in th.